Soluble CD163 performance as a suitable non-invasive biomarker of liver damage in chronically HCV and HCV/HIV infected subjects - Cairoli, Victoria (2022)
Macrophage activation plays a key role in liver disease progression. Soluble CD163 (sCD163) is a specific macrophage activation biomarker useful for clinical estimating damage severity and predicting outcome in different liver conditions. sCD163 performance as a non-invasive marker of liver damage was evaluated in plasma samples at time of biopsy in 120 patients with different hepatic conditions (56 HCV, 20 HCV/HIV, 10 HBV and 34 MAFLD). sCD163 values were compared with those of healthy donors and analyzed related to histological damage. sCD163 together with other clinical parameters were used to create a logistical regression model to predict significant fibrosis. Only patients with viral hepatitis showed higher sCD163 values compared to the control group (HCV p<0.0001; HCV/HIV p<0.0001; HBV p = 0.0003), but no significant differences regarding fibrosis stages were observed. The proposed model predicts fibrosis severity using the logarithm sCD163 concentration, platelet count and age, it demonstrated to be a good marker for the HCV monoinfected group (AUROC 0.834) and an excellent one for the HCV/HIV co-infected group (AUROC 0.997). Moreover, the model displayed a diagnostic performance similar to FIB-4 in HCV cases and FIB-4 and APRI in HCV/HIV coinfected cases, and it even managed to correctly classify some cases that had been misclassified. The proposed model is able to determine, in a non-invasive way, the liver fibrosis stage of HCV and HCV/HIV patients, so after validation, it could be used in a complementary way in the clinical practice whenever APRI and FIB-4 failed to determine damage severity in HCV and HCV/HIV cases.